Sunday at eight : presents a series of plays in aid of the National Joint Committee for Spanish Relief (publicity materials) - Kalkowska, Eleonore, 1883-1937 ; Ellis, Walter, 1874-1956
1939-03 017b-0013-005 292/946/17b/13(v)